Implementation of Problem-Based Learning to Improve Physics Learning Outcomes of Class X IPA-4 in SMA 59 - Samsul Bahri; Fauzi Bakri (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
This study aims to produce a problem-based learning (PBL) model to improve students' physics learning outcomes. The study was conducted from July to September 2016 at SMAN 59 Jakarta. The subjects of the study were students of class X IPA-4 which amounted to 36 people. The method used in this research is Collaboration Classroom Action Research (CCAR). The classroom action research model used is Carr & Kemmis model. The analysis of a learning is reflected in the next lesson. This study consists of three cycles, and each cycle consists of 2 to 6 meetings. From the result of research, the result of cognitive learning of students in cycle I obtained the average test value 56,2 with classical mastery 5,88%. In cycle II, the average value of 75.1 test with 55.88% classical completeness. In cycle III, the average score of 85.1 test with 91.8% classical completeness. Effective learning outcomes in cycle I, the average score 73.1 students with 20.59% complete learning. In cycle II, the average score of 77.1 students with 73.53% complete classical learning. In cycle III the average score 82.1 students with 100% complete learning. Psychomotor learning result in cycle I, average score 74,6 with 50% classical learning completeness. Cycle II, the average value of 80 with 100% complete classical completeness. Cycle III, the average value of 82.7 with 100% complete classical learning. It can be concluded that with the application of problem-based learning method can improve student learning outcomes of class X SMA Negeri 59 Jakarta Lesson Year 2015/2016.